Propofol Suppresses Proinflammatory Cytokine Production by Increasing ABCA1 Expression via Mediation by the Long Noncoding RNA LOC286367 - Ma, Xin; Wang, Teng; Zhao, Zhen-Long; Jiang, Yu; Ye, Shu (Mediators of Inflammation, 2018)
We previously reported that propofol upregulated the expression of ATP-binding cassette transporter subfamily A member 1 (ABCA1) via peroxisome proliferator-activated receptor gamma/liver X receptor in macrophage-derived foam cells. Here, we provide evidence that in addition to inducing ABCA1 expression, propofol represses proinflammatory cytokine production by increasing ABCA1 expression in a LOC286367-dependent manner. Western blot analysis showed that ABCA1 expression was elevated in macrophages by propofol treatment and this effect was markedly reduced by LOC286367 overexpression. Moreover, propofol treatment downregulated the production of the proinflammatory cytokines interleukin-6, tumor necrosis factor, and interferon gamma in lipopolysaccharide-stimulated macrophages by enhancing ABCA1 expression. Notably, propofol achieved this effect in a LOC286367-dependent manner. To the best of our knowledge, this is the first report of the mechanism in which propofol represses proinflammatory cytokine production mediated by ABCA1.